SAMLING, SAMLERE OG JÆGER-SAMLERE: Primitiv erhvervskultur og civilisationens fix - Veber, Hanne (Tidsskriftet Antropologi, 2001)
Collecting is about taking possession of the world, an exercise in how to make it one’s own, says James Clifford. He refers to the accumulation of material objects and to the collecting of exotic, curious, rare things that museum curators, philatelists, and art-lovers dedicate themselves to. Collecting, however, is not merely a pastime of an affluent elite. Comparative hunter-gatherer studies indicate that gathering serves to create an existential space of freedom – even in contexts where gathering appears primarily a subsistence activity. Gathering puts time and the social at play. It supports an escape from the workings of time and from the bonds of social relations and institutions that persist through time mediated by exchanges of objects. The article considers the trajectories of hunter-gatherer research and some of its results. It also points to its recent calling into question some of the fundamental assumptions on which the research has been based. Hunter-gatherer society, after all, may not be as distinct from other types of society as previously believed. This allows recognition that cultural phenomena previously considered distinct features of hunter-gatherer society figure equally in other types of society. Indeed, features known as “immediate return” or “demand sharing” and even “living in the present” may be adaptive forms of exchange and perception constituted at the interface of different – complex and less complex – types of social systems. These features then, are not special forms of exchange and ideology characteristic of hunter-gatherers seen as a model of pristine human life in groups. They are social strategies that sustain the survival of marginalized groups in contemporary societies. Indeed, “living in the present” and exchange in the form of “immediate return” or “sharing” helps encapsulated systems at the margins successfully escape total incorporation into surrounding, dominant, systems. A case in point is that of the Pajonal Ashéninka in the Peruvian Amazon where gathering is a necessary supplement to horticulture while simultaneously being considered a leisure activity by the Ashéninka themselves. From the point of view of the capitalist economy, this capacity of the Ashéninka to sustain themselves “from nothing” is an advantage in that it allows their being hired by local settlers for contract labor at very low costs to the employer. Gathering in this context helps the Ashéninka remain a relatively autonomous – and marginalized – indigenous group. At the same time, their availability as cheap reserve labor sustains a marginal form of capitalist production, in this case cattle-ranching in the rain forest, that threatens and gradually appropriates the resources on which the Ashéninka depend. Marginalized groups, be they Amazonian Indians, London prostitutes, Hungarian Gypsies, or Aegean Greek peasants may be shown to exhibit similar features of orientation to the present, a quasi-ritual space outside of durational time. They all appear to take a “natural” abundance for granted and to forage for their subsistence. They develop modes of life oriented towards the present and see no need to store for the future. In this way the structural insecurity that is part and parcel of their marginalized condition is transformed into an active focus on a celebration of immediate consumption in the present. The marginalized may experience themselves as free and autonomous people to whom freedom from material possessions and disengagement from institutions that organize long-term social reproduction is an existential choice. The marginalized position, and the particular form of identity it allows, however, is peculiarly vulnerable to appropriation by others. Despite the appearance of an autonomous way of life, it is hardly an independent social phenomenon. Rather, it is a product as much as the object of a dual process of incorporation and marginalization. In the end, the really interesting question concerns the role of an orientation towards the present tied to specific behavior in any type of society in particular limited contexts, be they gathering for subsistence, shopping for fun, scavenging, collecting beautiful art, or gathering rare sightings of birds as a leisure time devotion. These forms of behavior are rarely experienced as economic activity. Rather they are seen as forms of pleasure and fun, modes of taking possession of the world. They signal freedom of choice – yet, an imagined freedom. “Gathering” in whatever form it takes always involves substance, material items, that subsequently will be arranged, distributed or consumed. As an act of dealing with something that endures beyond its experience by the practitioner, gathering is a good place to unite loose objects, ends, perceptions and research interests.